Tumbuhan Bidara Dalam Al-Qur’an Dan Manfaatnya Bagi Kehidupan : (Kajian Tahlili QS. Al-Waqi’ah/56: 27-31) - usman, ilham; Nurliana; Rahmat Nurdin (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2023)
Abstract This article discusses the bidara plant (sidr)listed in QS. Al-Wa>qi’ah/5: 27-31. This research is a qualitative research that is bibliographical. The results of this study show that in . Al- Wa>qi’ah/56: 27-31, describes some of the pleasures obtained by the right, namely being among the bidara plants that are arranged with their beauty and a very wide shade in all places, running water whenever desired, sweet fruits of various kinds that exist, such is the reward for those who have done good while on earth. Bidara plantsare plants that have many benefits among them: as a spiritual medicine, beauty medicine, as afever reliever and can reduce diabetes, can treat wounds and launch the digestive system, not only that the bidara plant in becoming a business opportunity that can improve the economy of the people. Keywords: Al-Qur’an, Bidara, skincare, remaja